3p+7 = 16+2p 3p-2p = 16-7 p = 9
-24
9/15 + 10/15 = 1 and 4/15
Well, honey, if p equals 3, then 2p squared would be 2 times 3 squared. That's 2 times 9, which equals 18. So, the value of 2p squared when p equals 3 is 18. Math doesn't have to be complicated, darling.
In math problems without punctuation such as brackets, the standard convention in to solve from left to right. Therefore, you would solve the problem 15-3 times 4 plus nine like by three actions. 15-3 equals 12; 12 times 4 equals 48; 48 plus 9 equals 57.
3p+7 = 16+2p 3p-2p = 16-7 p = 9
First, set up the equation you are given: 15 - 2p = 9 Subtract 15 from each side of the equation: 15 -2p - 15 = 9-15 Then, you should have: -2p = -6 Divide each side by -2: (-2p)/(-2) = (-6/-2) Solve for p: p = 3
The commutative property.
-9
No! It equals 15, but 9-6=3.
25+15=40+9=49
2p - 9 = 5p + 12 subtract 2p fom both sides -9 = 3p +12 subtract 12 from both sides -21 = 3p divide both sides by 3 -7 = p
Yes, 9+6 is 15.
24 24 + (-15) = 9
-9
15
it equals 15